McCall Glacier, Alaska - Ohio State University (American Geographical Society of New York, 1959)
Blueline print.; Relief shown by contours and spot heights.; Folded into "IGY Project 4.11 report no. 11 Map of the McCall Glacier, Brooks Range, Alaska" by Dr. Arthur J. Brandenberger, July 1959. Color 1:5,000